Predictors of multivessel involvement in patients under 40 years of age receiving primary PTCA for STEMI (Annals of Medical Research, 2021)
Aim: The angiographic features of myocardial infarction in young patients and the factors affecting these features differ from those in elderly patients and have not been fully established. The aim of this study was to investigate the factors involved in the development of multivessel disease in patients aged 40 years or younger with ST-segment elevation myocardial infarction (STEMI).Material and Methods: A total of 148 patients aged 40 years or younger who underwent primary percutaneoustransluminal coronary angioplasty for STEMI were included in the study. The demographic features, angiographic features, biochemical data and risk factors of the patients were reviewed retrospectively. Results: Assessment of the risk factors showed that 91.2% of the patients were male, 73% were smokers, 56.8% were hyperlipidemic, 36.1% were hypertensive and 23.1% had diabetes mellitus. A positive family history was present in 31.1% of the patients. Hyperlipidemia was significantly more common (p=0.008) and the hemoglobin values were significantly lower (p0.001) in the patients with multivessel disease than those with single-vessel disease. Anemia was also significantly more prevalent in the patients with multivessel disease (p0.001).A multivariate regression analysis showed that anemia was associated with a 21.740-fold increase(95% CI: 2.921-161.817; p=0.003)in the likelihood of developing multivessel disease, irrespective of other risk factors, while hyperlipidemia was associated with a 3.742-fold increase (95% CI: 1.104-12.679; p=0.034) and male sex was associated with a 9.390-fold increase (95% CI: 1.019-86.570) (p=0.048).Conclusion: Anemia, hyperlipidemia and male sex are associated with multivessel disease in STEMI patients aged 40 years or younger.Keywords: Anemia;hyperlipidemia; multivessel; young myocardial infarction.